Impact of high technology on esthetics - the aerospeace influence - Anca Rugescu; Radu D. Rugescu (IBSU Scientific Journal (IBSUSJ), 2009)
A more or less subliminal impact of the aerospace technology over the general art of design is revealed. Some of the most visible trends are related to the implicit perception of the best geometrical shapes and their esthetical perception and exploitation in arts of design. Examples are driven along a century-long time period of arts history.
Keywords: 330; Esthetics; art of design; aerospace; high technology; mimetic